Modelling Blast Effects on a Reinforced Concrete Bridge - Markellos Andreou; Anastasios Kotsoglou; Stavroula Pantazopoulou (Advances in Civil Engineering)
The detailed investigation of blast phenomena and their catastrophic effects on existing structures are the main objectives of the present paper. It is well known that blast phenomena may be characterized by significant complexity, often involving complicated wave propagation effects as well as distinguishable material behaviors. Considering the above and in an attempt to provide a simplified modelling approach for the simulation of blast effects, a novel procedure is presented herein based on well-established methodologies and common engineering practices. In the above framework, firstly, the “predominant” deformation shape of the structure is estimated based on elastic finite element simulations under blast loads and then the structural response of the system is evaluated as a result of common computational beam-element tools such as displacement-based pushover analysis. The proposed methodology provides an immediate first estimation of the structural behavior under blast loads, based on familiar engineering procedures. A two-span reinforced concrete bridge was thoroughly investigated and the results provide insightful information regarding the damage patterns and localization.